PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PERPAJAKAN MELALUI PENERAPAN UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Suranta Ramses Tarigan; Syafruddin Kalo; Bismar Nasution; Sunarmi Sunarmi (USU LAW JOURNAL, 2014)
ABSTRACT Tax is the biggest revenue resources for a country. Tax criminal act results in inflicting loss to the country itself. Law on tax has been amended for three times until the enactment of Law No.28/2007 as the Third Amendment of Law No.6/1983 on General Provision and Taxation Procedures. The other law that can be applied as the form of seriousness in preventing and eradicating tax crimes is through the application of Law No.8/2010 on Money Laundering Perevention and Eradication as the policy of government to prevent and eradicate the criminals especially the tax criminals that they cannot practice money launderinh anymore. Keywords: Tax Criminal Act,  Money Laundering Criminal Act